ANALYSIS OF METHODS FOR DIGITAL TERRAIN MODELING BASED ON SPATIAL INTERPOLATION (Part 1) - Hunko, І. (Municipal economy of cities. Series: «Economy science», 2023)
Digital Elevation Model (DEM) is an important component of geodetic works, which allows reproducing the earth's surface in digital form with a certain level of detail. Various methods are used to construct DEMs, among which it is worth noting the methods based on spatial interpolation. One advantage of spatial interpolation is the ability to take into account the uneven distribution of points on the earth's surface, which provides a more accurate DEM. With the spread of high-precision geodetic instruments and technologies such as GPS and LiDAR, the methods of constructing DEMs have significantly improved. Modern methods include interpolation of curved surfaces, smoothing methods that reduce noise and random errors, and adaptive filtering methods that can detect and correct data anomalies. In the field of geodesy, digital elevation models are an essential element in performing measurements and creating project documentation for construction. The purpose of this article is to analyze existing methods for constructing digital elevation models and to compare them to choose the best one. For the analysis, the widely known geoinformation system package Surfer was selected, which contains a sufficiently large number of deterministic methods and a geostatistical method based on spatial interpolation. The Golden Software Surfer geoinformation system is currently the industry standard for constructing graphical representations of two-variable functions. An unbeatable advantage of the program is its built-in spatial interpolation algorithms, which allow creating digital surface models with high quality for spatially unevenly distributed data. The Surfer program provides 12 different methods of spatial interpolation. For the analysis, a random fragment of a topographic map was taken, which was previously digitized and exported in ASCII format with ready-made coordinates for constructing a DEM. However, only 6 out of the 12 methods that could more accurately reflect the real relief situation were further analyzed based on these topographic data, namely Kriging, Triangulation with Linear Interpolation, Radial Basic Function, Natural Neighbor, Modified Shepard`s Method and Minimum Curvature.